Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.